Strategi Pemasaran Produk Tabungan Seulanga Ib pada PT. Bank Aceh Syariah Capem Lhok Nibong - Jamali; Wahyuni, Eka (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
This study aims to determine the mechanism for opening Seulanga Ib savings and marketing strategies at PT Bank Aceh Syariah Capem Lhok Nibong. The type of data used in this study is primary data. Data collection techniques were carried out through Field Research with direct observation and interview methods on the target object, namely Bank Aceh Syariah Capem Lhok Nibong, Pante Bidari District, East Aceh Regency in order to obtain data that was in accordance with actual conditions in the field. The data obtained are presented descriptively. The results obtained by K from this study are that there is a mechanism for opening a Seulanga iB savings account, the conditions that must be attached and the conditions for opening a Seulanga iB savings account, including: 1) Submit a photocopy of a valid identity card such as an ID card or driver's license. 2) Fill in the font of the Seulanga iB savings form. 3) The initial deposit for opening a Seulanga Savings account is IDR 100,000 (one million rupiah) for the next deposit, a minimum of IDR 100,000 (one hundred thousand rupiah). The marketing strategy carried out by PT. Bank Aceh Syariah Capem Lhok Nibong in marketing the Seulanga iB Savings product is carried out in various ways including: a) Direct Selling, b) Cross Selling, c) Open Table, d) Advertising, and e) Sales Promotion.